The Absence of Constitutional Complaints in the Authority of the Constitutional Court Regarding the Protection of Public Benefit Rights in Indonesia - Dinda Rambe (NUSANTARA: Journal Of Law Studies, 2023)
The majority of constitutional complaints that enter the Constitutional Court are constitutional, but because they are not meant to be the authority of legal examination of the 1945 UUD, the Court often rejects them and allows them to take place "justiced delayed". This journal will dig deeper into some of the differences of previous research, namely the impact of the absence of a Constitutional Complaint on the protection of citizens' rights. This research is a library study, using secondary data sources. The research typology used in this study is explanatory. In this study, the study will focus on the theoretical and practical studies related to the impact of the absence of constitutional complaint legal mechanisms in Indonesia. While the data analysis methods used are qualitative, they are more focused on trying to interpret a particular situation. The absence of a legal effort against the constitutional complaint that is within the jurisdiction of the Constitutional Court would diminish Indonesia's legitimacy as a modern democratic state of law because of the absence in the public of legal efforts to question the treatment of the ruling authority that allegedly violates a person's constitutional rights.